Peran Pendidikan Inklusi dalam Membentuk Karakter Peserta Didik di Lembaga Pendidikan - Andi Herlina Gusnarib A. Wahab; Hikmatur Rahmah (EQUALITY: Journal of Gender, Child, and Humanity Studies, 2024)
Inclusive education focuses on student services that can meet the needs of inclusive students. However, it is not specifically for children with special needs, but for all students because they have diverse characteristics. The purpose of this study is to examine the role of inclusive education in shaping the character of students in educational institutions. By using this qualitative Library-Based research method, which refers to the use of media to collect library materials such as books, journals, and articles that will help solve research problems. While the results of this study obtained that inclusive education teaches students to appreciate differences and empathize with others, can improve social skills, form strong characters, encourage independence, improve academic achievement, Education for real life. It is hoped that through inclusive education it can enrich the learning experience for all students, form better characters and be ready to face the challenges of life.